2010
DOI: 10.2478/s11756-010-0063-1
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors influencing the occurrence of freshwater snails in woodland water bodies

Abstract: Studies were carried out in eight woodland water bodies that are situated in an urbanised area of Southern Poland (Upper Silesia). The aim of this study was to determine the influence of auto-and allochthonous plant detritus and exposure to sunlight on the structure of snail communities in woodland ponds. Among some physico-chemical water parameters, pH influenced the occurrence of snails, whereas sunlight caused an increase in diversity of the snail communities. In the total snail collection, 72.1% of specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
(11 reference statements)
2
13
0
Order By: Relevance
“…For this reason, woodland ponds create specific habitats for the occurrence of invertebrates including freshwater snails. This was also confirmed in previous studies (Spyra 2010(Spyra , 2011. In this research, we found G. crista in only six ponds.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…For this reason, woodland ponds create specific habitats for the occurrence of invertebrates including freshwater snails. This was also confirmed in previous studies (Spyra 2010(Spyra , 2011. In this research, we found G. crista in only six ponds.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies that were carried out in woodland ponds (Spyra 2010) demonstrated that exposition to sunlight had no impact on the occurrenceof G. crista, and that individuals of this species were much more numerous in the autochthonous plant matter (Typha debris) as compared to allochthonous. Phragmites litter is nutritionally poor and an unfavorable food source for invertebrate detritivores (Kulesza et al 2008).…”
Section: Gyraulusmentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, in this survey, the correlation of the occurrence of P. subtruncatum and the organic matter content in bottom sediments may also be explained by alimentation preferences. According to Spyra (2010), freshwater snails preferred sites that mainly had allochthonic detritus in anthropogenic reservoirs (Southern Poland, Upper Silesia): Radix balthica was more frequent on allochthonic detritus (F = 87.5%),…”
Section: Discussionmentioning
confidence: 99%
“…hypnorum is known for its distribution in most European countries (Welter-Schultes, 2012, 2013 and North America (Dillon et al, 2006). But in some countries, the numbers of these snails were small such as in woodland ponds from Southern Poland (Spyra, 2010) and a few ponds of the upper Rhine valley (Mosimann, 2000;Bauer and Ringeis, 2002). This physid colonizes small and temporary waterbodies rich in vegetation, located in lowlands.…”
Section: Introductionmentioning
confidence: 99%